Phylogenetic relationships of the neon tetras Paracheirodon spp. (Characiformes: Characidae: Stethaprioninae), including comments on Petitella georgiae and Hemigrammus bleheri - Bittencourt,Pedro Senna (2020)
ABSTRACT Neon tetras (Paracheirodon spp.) are three colorful characid species with a complicated taxonomic history, and relationships among the species are poorly known. Molecular data resolved the relationships among the three neon tetras, and strongly supported monophyly of the genus and its sister taxon relationship to Brittanichthys. Additionally, the sister-taxon relationship of the rummy-nose tetras Hemigrammus bleheri and Petitella georgiae was strongly supported by molecular and morphological data. Therefore, we propose to transfer the rummy-nose tetras H. bleheri and H. rhodostomus to the genus Petitella. Furthermore, Petitella georgiae is likely to be a species complex comprised of at least two species.